2017
DOI: 10.3389/fpls.2017.00370
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes of Ralstonia solanacearum during Root Colonization of Solanum commersonii

Abstract: Bacterial wilt of potatoes—also called brown rot—is a devastating disease caused by the vascular pathogen Ralstonia solanacearum that leads to significant yield loss. As in other plant-pathogen interactions, the first contacts established between the bacterium and the plant largely condition the disease outcome. Here, we studied the transcriptome of R. solanacearum UY031 early after infection in two accessions of the wild potato Solanum commersonii showing contrasting resistance to bacterial wilt. Total RNAs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 84 publications
4
15
0
Order By: Relevance
“…In addition, on close examination of the publicly available transcriptome data of R. solanacearum strains GMI1000 and UW551 derived from in planta and rich-medium growth (4), it was found that pfk-1 and gnd gene expression levels were not reported (while several other genes such as those of the ED pathway were expressed), potentially owing to their absence. Similarly, the transcriptome analysis by Puigvert et al has no reports of gnd and pfk-1 genes in homologous gene analysis of R. solanacearum strains whereas ED pathway genes were reported (26). These observations further supported our findings that the gnd and pfk-1 genes are inactive or altogether absent in R. solanacearum and that mainly glucose oxidation bypasses glycolysis and OxPPP in favor of the ED pathway and non-OxPPP.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, on close examination of the publicly available transcriptome data of R. solanacearum strains GMI1000 and UW551 derived from in planta and rich-medium growth (4), it was found that pfk-1 and gnd gene expression levels were not reported (while several other genes such as those of the ED pathway were expressed), potentially owing to their absence. Similarly, the transcriptome analysis by Puigvert et al has no reports of gnd and pfk-1 genes in homologous gene analysis of R. solanacearum strains whereas ED pathway genes were reported (26). These observations further supported our findings that the gnd and pfk-1 genes are inactive or altogether absent in R. solanacearum and that mainly glucose oxidation bypasses glycolysis and OxPPP in favor of the ED pathway and non-OxPPP.…”
Section: Discussionsupporting
confidence: 90%
“…This hypothesis is also supported by the wider range of metabolized amino acids by Dso3337 revealed by the metabolic assays. Our approach analysing expression on tuber slices contrasts to those reported for A. tumefaciens (González‐Mula et al, ), P. syringae (Yu et al ., ) and R. solanacearum (Jacobs et al ., ; Puigvert et al ., ), in which bacteria were recovered from the colonized plant tissues or symptoms. However, some comparisons remain possible on the resource exploitation strategy: a generalist behavior (copiotrophy) in the case of the Dickeya and Agrobacterium pathogens that both exploit abundant and diversified plant metabolites in macerated tissues and plant tumours respectively; a specialist behavior (oligotrophy) in the case of the P. syringae and R. solanacearum that exploit a more limited variety of metabolites that are present on leaf surface and in leaf or root interior and plant vessels.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the expression profile of the cas genes from RSSC strains may be different in the natural environment. Previous transcriptomic studies have shown that gene expression profiles of RSSC strains drastically change in plants when compared with growth in a synthetic rich medium (Ailloud et al , ; Jacobs et al , ; Puigvert et al , ).…”
Section: Discussionmentioning
confidence: 99%